Assessing Sunscreen Lifecycle to Minimize Environmental Risk Posed by Nanoparticulate UV-Filters – A Review for Safer-by-Design Products - Labille, Jérôme; Catalano, Riccardo; Slomberg, Danielle; Motellier, Sylvie; Pinsino, Annalisa; Hennebert, Pierre; Santaella, Catherine; Bartolomei, Vincent (Frontiers in Environmental Science, 2020)
Sunscreens are of emerging concern regarding environmental effect. After leaving the skin either through bathing or washing, the ingredients contained in the product formulation can be released into rivers, lakes, seashores, and/or sewage treatment plants. Nanomaterials used as UV-filters are of particular concern in this context as they may have a negative effect on these systems. To assess the risks posed, the exposure and hazard of nanoparticulate UV-filters must be considered through the entire lifecycle of the sunscreen product. This includes not only usage, but also manufacturing and disposal at the end of life of the product, as some nanomaterials may be released into the environment at each stage. This includes also developing relevant approaches that take into account realistic scenarios of environmental release and fate. Nanoparticulate UV-filters typically consist of a mineral nanoparticle core (TiO2 or ZnO) coated with surface layers aimed at optimizing the dispersion in the formulation and at supressing any photo-sensibility. This coating plays a key role in the associated risk since it affects the nanoparticle surface properties, which control both fate and hazard. At present, knowledge gaps remain regarding the safety of nanomaterials used in sunscreen, as very few studies have focused on real sunscreen filters and formulations throughout their lifecycle so far. A literature review is proposed here from the design of nanoparticulate UV-filters and formulations, to the release, fate, and effect in the different compartments encountered along the product lifecycle. The resulting state of the art highlights knowledge gaps and will likely help regulators, manufacturers, and consumers choose appropriate guidance. By considering each development stage of the sunscreen, from the choice of the UV-filter(s) and its (their) integration into a cosmetic formulation to the knowledge of the risk involved in this choice all along the product lifecycle, an eco-design approach can be achieved where release or toxicity are reduced. Sustainability can thus be accounted for, during the design process, by making the appropriate choices (in advance) that help minimize or prevent the environmental impact of the sunscreen.